Contribution of surface silanization process on mechanical characteristics of TPU-based composites involving feldspar and quartz minerals - Bouzmane, Hajar; Tirkes, Suha; Yılmaz, Volkan Murat; Tayfun, Ümit; Tirkes, Seha; Yılmaz, Volkan Murat; Tayfun, Ümit (Wiley, 2023)
In this study, quartz and feldspar powders were surface treated using a silane coupling agent to achieve a more compatible mineral surface with the polymer matrix. Details of surface characteristics of minerals were examined by energy-dissipative X-ray spectroscopy, contact angle measurements, and infrared spectroscopy. Thermoplastic polyurethane-TPU was compounded with minerals using the melt-blending technique. Mechanical, thermo-mechanical, melt-flow, and morphological characterizations of TPU and relevant composites were performed by utilizing tensile and Shore hardness tests, dynamic mechanical analysis (DMA), melt flow index (MFI) measurements, and scanning electron microscopy (SEM), respectively. Water repellency of TPU and composites were also evaluated experimentally. Effects of surface treatments were discussed by comparing the results of composites filled with pristine and modified minerals. Results revealed that enrichment of quartz and feldspar surfaces confer mechanical and thermo-mechanical performance of composites. Mineral inclusions caused no drastic changes to the MFI parameter of TPU. The silane layer on the mineral surface displayed a barrier effect to water uptake of composites. Homogeneous dispersion and improved interfacial adhesion of mineral particles to the TPU phase were confirmed with help of SEM observations. Quartz exhibited slightly higher performance thanks to its silica-rich composition. The findings of this research exhibited the considerable influence of the silane layer on the mineral surface on the mechanical performance of TPU-based composites.
Keywords: Feldspar; Polymer Composites; Polyurethanes; Quartz; Surface Modification